Analysis of Open and Closed Proportional System General Elections From a Democratic Perspective - Manika, Agus Surya; Subawa, I Made; Kartika, I Gusti Ayu Putri; Resen, Made Gde Subha Karma (PT FORMOSA CENDEKIA GLOBAL, 2024)
The implementation of general elections is one of the characteristics of a democratic country as a form of people's sovereignty. There are various types of general election systems throughout the world, including open and closed proportional systems. The normative legal method is based on the absence of norms in Law of the Republic of Indonesia Number 7 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 1 of 2022 concerning Amendments to Law Number 7 of 2017 concerning General Elections into Law, where this Law only regulates the open proportional general election system and there is no regulation on the closed proportional system. The problem discussed in this study is how is the analysis of the open and closed proportional general election system from a democratic perspective? and which general election system is better to use for Indonesia and other democratic countries?.